MANAJEMEN MADRASAH DALAM POLA PEMBELAJARAN QUANTUM TEACHING - Milahtul latifah; Siti Ulfa Mamdudah (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2023)
In general, most students are less active in learning which can be seen when students are asked a question directly by the teacher, students are still confused about answering it, when asked about material that has not been understood from the material being taught, it turns out that only one student can answer it. This shows that students' emotional intelligence and intellectual intelligence are still low because the application of the learning methods used by the teacher is less precise and less varied. The purpose of this study is to find out about Madrasah Management at MA Pondok Pesantren Al-Itqon Bogor, to find out Quantum Teaching Learning at MA Pondok Pesantren Al-Itqon Bogor, and to see how the implementation of teaching materials through Quantum Teaching Learning Patterns at MA Pondok Pesantren Al-Itqon Bogor. The method used is descriptive qualitative method. The implementation of special service management at MTs Al-Itqon Bogor has been very good in special services for students, starting from the library, health services, canteens, and guidance and counseling services. All special services at MTs Al-Itqon Bogor are good and satisfy the students as customers of MTs Al-Itqon Bogot. The effectiveness in this Madrasah Institution seeks all ways to be able to implicate the teaching of the Al-Qur'an hadith through the Quantum Teaching learning method so that the learning process can be quality and effective. One form of learning is by creating classrooms, dividing study groups and listening murotal verses of the Qur’an